Activated Platelets Autocrine 5-Hydroxytryptophan Aggravates Sepsis-Induced Acute Lung Injury by Promoting Neutrophils Extracellular Traps Formation - Huang, Yumeng; Ji, Qian; Zhu, Yanyan; Fu, Shengqiao; Chen, Shuangwei; Chu, Liangmei; Ren, Yongfei; Wang, Yue; Lei, Xuan; Gu, Jia; Tai, Ningzheng; Liu, Dadong (Frontiers in Cell and Developmental Biology, 2022)
Excessive neutrophil extracellular trap (NET) formation is an important contributor to sepsis-induced acute lung injury (ALI). Recent reports indicate that platelets can induce neutrophil extracellular trap formation. However, the specific mechanism remains unclear. Tph1 gene, which encodes the rate-limiting enzyme for peripheral 5-hydroxytryptophan (5-HT) synthesis, was knocked out in mice to simulate peripheral 5-HT deficiency. Cecal ligation and puncture (CLP) surgery was performed to induce sepsis. We found that peripheral 5-HT deficiency reduced NET formation in lung tissues, alleviated sepsis-induced lung inflammatory injury, and reduced the mortality rate of CLP mice. In addition, peripheral 5-HT deficiency was shown to reduce the accumulation of platelets and NETs in the lung of septic mice. We found that platelets from wild-type (WT), but not Tph1 knockout (Tph1−/−), mice promote lipopolysaccharide (LPS)-induced NET formation. Exogenous 5-HT intervention increased LPS-induced NET formation when Tph1−/− platelets were co-cultured with WT neutrophils. Therefore, our study uncovers a mechanism by which peripheral 5-HT aggravated sepsis-induced ALI by promoting NET formation in the lung of septic mice.